2010
DOI: 10.1007/s00284-010-9629-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Cationic Porphyrin on Pseudomonas aeruginosa Biofilms

Abstract: Current studies have indicated the utility of photodynamic therapy using porphyrins in the treatment of bacterial infections. Photoactivation of porphyrins results in the production of singlet oxygen ((1)O(2)) that damages biomolecules associated with cells and biofilms, e.g., proteins, polysaccharides, and DNA. The effect of a cationic porphryin on P. aeruginosa PAO1 biofilms was assessed by exposing static biofilms to 5,10,15,20-tetrakis(1-methyl-pyridino)-21H,23H-porphine, tetra-p-tosylate salt (TMP) follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 21 publications
6
71
0
3
Order By: Relevance
“…According to CV staining assay, CUR-mediated PDT not only reduced the metabolic activity of Candida biofilms, but also decreased the biofilm biomass of all species evaluated. It has previously been suggested that PDT can target bacterial biofilms by killing the cells and disrupting biofilm architecture [41]. Light micrographs performed by Goulart et al [42] showed that PDT was able to detach bacterial cells from the well in which biofilms were formed.…”
Section: Discussionmentioning
confidence: 99%
“…According to CV staining assay, CUR-mediated PDT not only reduced the metabolic activity of Candida biofilms, but also decreased the biofilm biomass of all species evaluated. It has previously been suggested that PDT can target bacterial biofilms by killing the cells and disrupting biofilm architecture [41]. Light micrographs performed by Goulart et al [42] showed that PDT was able to detach bacterial cells from the well in which biofilms were formed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that AgNP activity is strongly dependent on the size [46,47]. In fact, the bactericidal activity of AgNPs of smaller dimensions (<30 nm) was found to be optimal against Staphylococcus aureus and Klebsiella pneumoniae [49]. Smaller nanoparticles seem to have a superior ability to penetrate into bacteria.…”
Section: Salmonella Typhimentioning
confidence: 99%
“…Alteration of membrane [28,41,47] Listeria monocytogenes Morphological changes, separation of the cytoplasmic membrane from the cell wall, plasmolysis [47] Micrococcus luteus Alteration of membrane [28] Nitrifying bacteria inhibits respiratory activity [31] Pseudomonas aeruginosa Irreversible damage on bacterial cells; Alteration of membrane permeability and respiration [17,28,32,33,36,[41][42][43][44][48][49][50] Proteus mirabilis Alteration of cell wall and cytoplasm. [43,44] …”
Section: Klebsiella Pneumoniaementioning
confidence: 99%
“…Tetracationic porphyrin TMPyP4 was used on Pseudomonas aeruginosa biofilms, and caused direct cell killing as well as detachment of the biofilm after light activation. The enhanced killing of the cells when TMPyP was used in the combination with tobramycin indicates a light-independent mechanism, and it has been suggested that the two mechanisms together could be employed for the treatment of biofilms and infections not easily reachable by light (Collins et al 2010).…”
Section: Combination Strategies In Pdtmentioning
confidence: 99%